Social Media Marketing And Destination Branding: Current Research Trend And Direction For Future Research - Sandra J.R. Kainde; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Social media has become a pivotal tool in shaping destination branding strategies, profoundly influencing tourists’ perceptions and behaviors. This study aims to systematically review the existing literature to examine the intersection of social media marketing and destination branding, with the goal of identifying dominant research themes, theoretical gaps, and future research directions. Utilizing a Systematic Literature Review (SLR) methodology, the study analyzes peer-reviewed journal articles published between 2010 and 2025, sourced from the Scopus database. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, rigorous screening, data extraction, and synthesis were applied. The final dataset includes 103 relevant studies, with 66 articles subjected to in-depth bibliometric and content analysis. VOSviewer was employed for data visualization and thematic clustering. The findings reveal eight key thematic clusters: Social Media and Co-Creation, Sustainability in Branding, Digital Engagement, Emotional and Experiential Branding, Place Identity, and Brand Equity. The results offer critical insights into how social media facilitates brand co-creation and emotional resonance in destination marketing and highlight underexplored areas for future investigation. This review contributes to both academic scholarship and practical strategy development by offering a comprehensive thematic map of the evolving discourse on social media and destination branding.